2017
DOI: 10.6065/apem.2017.22.1.27
|View full text |Cite
|
Sign up to set email alerts
|

Change in body mass index and insulin resistance after 1-year treatment with gonadotropin-releasing hormone agonists in girls with central precocious puberty

Abstract: PurposeGonadotropin-releasing hormone agonist (GnRHa) is used as a therapeutic agent for central precocious puberty (CPP); however, increased obesity may subsequently occur. This study compared body mass index (BMI) and insulin resistance during the first year of GnRHa treatment for CPP.MethodsPatient group included 83 girls (aged 7.0–8.9 years) with developed breasts and a peak luteinizing hormone level of ≥5 IU/L after GnRH stimulation. Control group included 48 prepubertal girls. BMI and insulin resistance-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
13
2
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 30 publications
3
13
2
3
Order By: Relevance
“…However, results in reports on the changing patterns of BMISDS during GnRHa treatment after classifying the CPP subjects into BMI-based normal-weight and overweight groups are relatively consistent. As in the present report, most such stratified studies show that the normal-weight group shows increased BMISDS during GnRHa therapy, but, no similar increase in the overweight group [ 12 , 17 , 18 , 24 ]. Then, what is the cause of different BMISDS changes between the 2 groups?…”
Section: Discussionsupporting
confidence: 74%
“…However, results in reports on the changing patterns of BMISDS during GnRHa treatment after classifying the CPP subjects into BMI-based normal-weight and overweight groups are relatively consistent. As in the present report, most such stratified studies show that the normal-weight group shows increased BMISDS during GnRHa therapy, but, no similar increase in the overweight group [ 12 , 17 , 18 , 24 ]. Then, what is the cause of different BMISDS changes between the 2 groups?…”
Section: Discussionsupporting
confidence: 74%
“…Similarly, the normal weight group had an incrementally increased WHtR at visits 2 and 3, although the values were not significantly different when we compared visits 1 and 4. Another domestic study has revealed similar tendencies 26) , although the present study involved a longer follow-up after the treatment had been discontinued, which allows us to conclude that abdominal obesity did not develop after termination of the GnRHa treatment.…”
Section: Discussionsupporting
confidence: 67%
“…Similarly, Yoon et al 27) reported a remarkable increase in zBMI (−0.15±0.72 vs. −0.08±0.66, P <0.05) in the normal weight group after 1 year of GnRHa treatment, although no significant change was observed in the overweight/obese group (1.69±0.51 vs. 1.60±0.48, P >0.05). Furthermore, Park and Kim 26) reported a significant increase in zBMI during the first year of GnRHa treatment (−0.1±0.7 vs. 0.1±0.8, P < 0.001), with no change in the overweight/obese group, although an increase was detected in their insulin resistance index. Nevertheless, it is important to note that the reported correlations between BMI and obesity were limited by the studies' small sample size or an insufficient follow-up period 7 21 25) .…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Precocious Puberty (PP), physical and hormonal manifestations of early pubertal development which occurs at an earlier age than the normally accepted limit (3). PP is defined as the development of breast growth (thelarche) in girls before the age of 8, which is the initial limit and the initiation of testis growth before 9 years of age in males (4).…”
Section: Introductionmentioning
confidence: 99%